Adiponectin and its receptors in non-alcoholic steatohepatitis. Issue 1 (10th December 2004) - Kaser, S; Moschen, A; Cayon, A; Kaser, A; Crespo, J; Pons-Romero, F; Ebenbichler, C F; Patsch, J R; Tilg, H
Abstract : Background: Adiponectin, an adipocyte derived polypeptide, has been shown to alleviate steatosis and inflammation in mice with non-alcoholic fatty liver disease. Aim: In the present study, we wished to define liver expression of adiponectin and its receptors in morbidly obese patients undergoing bariatric surgery. Patients with non-alcoholic steatohepatitis (NASH) or simple steatosis were investigated to test whether dysregulation of this system might be involved in these disorders. Patients and methods: Liver mRNA expression of adiponectin and its recently cloned receptors RI and RII (adipoRI and adipoRII) were analysed by fluorescence based real time polymerase chain reaction in 13 patients with NASH and nine with simple steatosis. Adiponectin and adipoRII protein expression were assessed by immunohistochemistry in a subgroup of patients. Results: Adiponectin and adipoRII mRNA expression were significantly reduced in liver biopsies of patients with NASH compared with simple steatosis while no difference was found in adipoRI mRNA expression. In NASH, adipoRII mRNA expression was negatively correlated with serum aspartate aminotransferase levels, serum alanine aminotransferase levels, and grade of fibrosis. Liver adiponectin protein expression was mainly found in endothelial cells of portal vessels and liver sinusoids whereas adipoRII expression was seen in hepatocytes only. Adiponectin and adipoRII staining were lower in biopsies of subjects with NASH compared with simple steatosis. Conclusion: Reduced hepatic expression of adiponectin and adipoRII might be of pathophysiological relevance in non-alcoholic fatty liver diseases.